ADAPTATION ATTITUDES TOWARD TELEAUDIOLOGY SCALE TO MALAY (MyATS-P) - Rashid, Mohd Fadzil Nor; Kar, Quar Tian; Maamor, Nashrah; Yen, Chong Foong (International Journal of Allied Health Sciences, 2019)
Introduction: Measuring the attitudes of audiologist towards teleaudiology before its implementation is very important. Several studies had developed questionnaires to investigate the usage of information communication technology (ICT), the effect on audiological services and the willingness among audiologist to implement teleaudiology. However, none of these questionnaires was in Malay version and applied for professional in Malaysia. In this regard, this present study aimed to adapt and validate the ‘Attitudes toward Teleaudiology Scale for Practitioners into Malay (MyATS-P)’. Methods: The English version of ATS-P was translated into Malay version by three qualified professionals and seven clinical professionals were invited to measure the content validity index (CVI). For reliability evaluation, 15 audiologists were invited to answer MyATS-P. Results: Item CVI (I-CVI) values for MyATS-P was found ranged from 0.86 – 1.00 and scale CVI (average of I-CVI) was found to be excellent (0.96). Statistically, Kuder Richardson 21 score was 0.81 for section 1 and Cronbach’s alpha were 0.88 for section 2, 0.91 for section 3 and 0.90 for section 4. Conclusions: The MyATS-P had demonstrated excellent CVI and acceptable reliability. This finding supports the use of the questionnaire in the local population.